Duchenne muscular dystrophy involves the myocardium and causes arrhythmia: Case report - Liu, Xuhan; Zhao, Wei; Shu, Shangzhi; Zhang, Weihua (Frontiers in Cardiovascular Medicine, 2022)
Background Patients with muscular dystrophy have mutations in the gene that can lead to severe muscle wasting, respiratory issues or heart failure between ages 30 and 40. Currently, there is no effective treatment for DMD-induced heart failure. Case presentation We report a patient with recurrent unexplained fever and muscle soreness was definitely diagnosed with DMD. An analysis of the patient's genetics revealed a nonsense mutation (C.1207G > T). His DMD was treated with hormones. Also, the patient's fever is under control because of hormone therapy. However, as the disease progresses, the heart structure and function gradually change, and eventually malignant arrhythmias occur. Conclusion We report a rare case of DMD involving the heart causing heart failure and malignant arrhythmia. Currently, no complete treatment is available for these patients, but our treatment regimen may benefit our patient and improve his outcomes.